2021
DOI: 10.3168/jdsc.2020-0020
|View full text |Cite
|
Sign up to set email alerts
|

Detection of cow hind-leg activity during milking by using a 3-dimensional accelerometer attached to the milking cluster

Abstract: Hind-leg activity during milking, as an indicator of welfare impairment, was recorded on 45 dairy cows during 2 milkings by using direct visual observations and a 3-dimensional (3D) accelerometer attached directly to the hook of each milking claw. Our study shows that the use of a 3D accelerometer attached to the milking cluster is a promising method to reliably estimate cow hind-leg movements. An automatic and objective detection of foot-lifting, stepping, and kicking behaviors allows analysis of the causes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…This therefore leads to an underestimation of the actual HLA by the sensor measurement. A comparison to results with direct observation from other studies is consequently not reliable [32].…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…This therefore leads to an underestimation of the actual HLA by the sensor measurement. A comparison to results with direct observation from other studies is consequently not reliable [32].…”
Section: Discussionmentioning
confidence: 87%
“…Nonetheless, other factors influencing this finding cannot entirely be excluded. The HLA was indirectly measured by a 3D-acceleration sensor attached to the milking cluster by applying the method published by Raoult et al [32]. These authors reported a mean HLA rate of 0.94 activities per minute during milking by direct observation and 0.86 activities per minute detected by the 3D-accelerometer.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations